Maternal Lead Exposure Impairs Offspring Learning and Memory via Decreased GLUT4 Membrane Translocation - Zhao, Zai-Hua; Du, Ke-Jun; Wang, Tao; Wang, Ji-Ye; Cao, Zi-Peng; Chen, Xiao-Ming; Song, Han; Zheng, Gang; Shen, Xue-Feng (Frontiers in Cell and Developmental Biology, 2021)
Lead (Pb) can cause an significant neurotoxicity in both adults and chidren, leading to the impairment to brain function. Pb exposure plays a key role in the impairment of learning and memory through synaptic neurotoxicity, resulting in the cognitive function. Researches have demonstrated that Pb exposure plays an important role in the etiology and pathogenesis of neurodegenerative diseases, such as Alzheimer’s disease. However, the underlying mechanisms remain unclear. In the current study, a gestational Pb exposure (GLE) rat model was established to investigate the underlying mechanisms of Pb-induced cognitive impairment. We demonstrated that low-level gestational Pb exposure impaired spatial learning and memory as well as hippocampal synaptic plasticity at postnatal day 30 (PND 30) when the blood concentration of Pb had already recovered to normal levels. Pb exposure induced a decrease in hippocampal glucose metabolism by reducing glucose transporter 4 (GLUT4) levels in the cell membrane through the phosphatidylinositol 3 kinase-protein kinase B (PI3K-Akt) pathway. In vivo and in vitro GLUT4 over-expression increased the membrane translocation of GLUT4 and glucose uptake, and reversed the Pb-induced impairment to synaptic plasticity and cognition. These findings indicate that Pb exposure impairs synaptic plasticity by reducing the level of GLUT4 in the cell membrane as well as glucose uptake via the PI3K-Akt signaling pathway, demonstrating a novel mechanism for Pb exposure-induced neurotoxicity.